Modern Teaching Methods - Qochqorova Zulfizar Abduxamid qizi; Nuriddinova Gulnoza Ro`zali qizi (Journal of Innovation in Education and Social Research, 2023)
This article is written as a comparative analysis to compare modern methods and old methods in teaching English today. Today, along with the relevance of the English language, the methods and methods of teaching it are also becoming relevant. This situation requires teachers to modernize and abandon old methods as soon as possible.